Cost Savings In Workshop Building Structures Through Value Engineering Approach Based On Cold-Formed Steel With Integration Of Life Cycle Costing And Risk Evaluation - Richard Austen Soegianto; Yusuf Latief (CV. AFDIFAL MAJU BERKAH, 2026)
Workshop building structures commonly use conventional steel materials known for their strength, but they pose challenges in terms of cost, transportation, and time efficiency—particularly in projects located in remote areas. This study aims to optimize the structural cost of Workshop buildings by integrating the approaches of Value Engineering (VE), the selection of Cold-Formed Steel (CFS) material, the Life Cycle Costing (LCC) method, and risk evaluation. VE is applied to identify the primary functions of the structure and propose more efficient alternatives without compromising performance. CFS is selected due to its lightweight nature, ease of transportation and installation, and suitability for remote project locations. The LCC method is used to assess total costs over the building's life cycle, including initial investment, maintenance, and residual value. Risk evaluation is conducted to identify potential technical, operational, and economic obstacles that may affect implementation success. The results show that the use of CFS through VE and LCC approaches can significantly improve cost efficiency compared to conventional steel structures. This approach not only reduces initial project costs but also saves long-term expenses through minimal maintenance and optimal service life. Risk evaluation supports more informed decision-making, making this integrated approach an effective strategy for designing economical, efficient, and sustainable Workshop structures.